2018
DOI: 10.1088/1748-605x/aade9d
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun vascular grafts fabricated from poly( L -lactide-co- ε -caprolactone) used as a bypass for the rabbit carotid artery

Abstract: The study involved the electrospinning of the copolymer poly(L-lactide-co-ε-caprolactone) (PLCL) into tubular grafts. The subsequent material characterization, including micro-computed tomography analysis, revealed a level of porosity of around 70%, with pore sizes of 9.34 ± 0.19 μm and fiber diameters of 5.58 ± 0.10 μm. Unlike fibrous polycaprolactone, the electrospun PLCL copolymer promoted fibroblast and endothelial cell adhesion and proliferation in vitro. Moreover, the regeneration of the vessel wall was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…PLCL shows good elasticity and biocompatibility and slow biodegradation [ 14 ]. In a rabbit animal model, the degradation rate of PLCL was approximately six months in vivo [ 15 ]. PU is well known for its mechanical properties and appropriate biocompatibility, especially for its high tensile strength and toughness, making it one of the most important synthetic polymers for the fabrication of vascular grafts [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLCL shows good elasticity and biocompatibility and slow biodegradation [ 14 ]. In a rabbit animal model, the degradation rate of PLCL was approximately six months in vivo [ 15 ]. PU is well known for its mechanical properties and appropriate biocompatibility, especially for its high tensile strength and toughness, making it one of the most important synthetic polymers for the fabrication of vascular grafts [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of the studies have been conducted on rats and rabbits. Moreover, there is a need for longer in vivo studies (>12 months) since the patency rate is still considerably lower than in autologous grafts ( Horakova et al, 2018 ).…”
Section: Tissue-engineered Vascular Graftsmentioning
confidence: 99%
“…A confluent layer of VSMCs was observed on the outer surface and were present on all layers of the dynamically cultured graft compared to just a few on the statically cultured one. Horakova et al [61] created a tubular graft from 70:30 PLCL. In vitro studies showed that PLCL scaffolds better supported viability and proliferation of 3 T3 mouse fibroblasts and endothelial cells after 14 days in static culture compared to PCL scaffolds.…”
Section: Poly(l-lactide-co-ε-caprolactone)-poly(l-lactide-co-ε-caprolactone)mentioning
confidence: 99%